The Development of Non-natural Type Nucleoside to Stabilize Triplex DNA Formation against CG and TA Inversion Site - Wang, Lei; Ling, Yong; Tian, Yan; Wang, Xiao; Sasaki, Shigeki; Taniguchi, Yosuke (Current Medicinal Chemistry, 2024)
Based on the sequence-specific recognition of target duplex DNA by triplexforming oligonucleotides (TFOs) at the major groove side, the antigene strategy has been exploited as a gene-targeting tool with considerable attention. Triplex DNA is formed via the specific base triplets by the Hoogsteen or reverse Hoogsteen hydrogen bond interaction between TFOs and the homo-purine strand from the target duplex DNA, leading to the established sequence-specificity. However, the presence of inversion sites, which are known as non-natural nucleosides that can form satisfactory interactions with 2′- deoxythymidine (dT) and 2′-deoxycytidine (dC) in TA and CG base pairs in the target homo-purine DNA sequences, drastically restricts the formation of classically stable base triplets and even the triplex DNA. Therefore, the design of non-natural type nucleosides, which can effectively recognize CG or/and TA inversion sites with satisfactory selectivity, should be of great significance to expanding the triplex-forming sequence. Here, this review mainly provides a comprehensive review of the current development of novel nonnatural nucleosides to recognize CG or/and TA inversion sites in triplex DNA formation against double-strand DNA (dsDNA).
Keywords: recognition